Imagined empires : a history of revolt in Egypt - Abul-Magd, Zeinab, 1976- (University of California Press, 2013)
Through a microhistory of a small province in Upper Egypt, this book investigates the history of five world empires that assumed hegemony in Qina province over the last five centuries. Imagined Empires charts modes of subaltern rebellion against the destructive policies of colonial intruders and collaborating local elites in the south of Egypt. Abul-Magd vividly narrates stories of sabotage, banditry, flight, and massive uprisings of peasants and laborers, to challenge myths of imperial competence. The book depicts forms of subaltern discontent against ""imagined empires"" t.